Bone Morphogenetic Protein 15 (BMP-15) Improves In Vitro Mouse Folliculogenesis - Jitjumnong, Jakree; Tang, Pin-Chi (Animals (Basel), 2023)
Multilayered secondary follicles were encapsulated in a 0.5% alginate matrix and cultured in a 3D culture system supplemented with bone morphogenetic protein 15 (BMP-15; 15 ng/mL) for 12 days. The in vitro development of ovarian follicles was evaluated. On day 12, the follicle diameter, follicle survival rate, and antrum formation rate were significantly higher for follicles cultured in BMP-15-supplemented medium than those cultured in regular medium. The percentage of ovulated metaphase II oocytes retrieved from follicles cultured in BMP-15-supplemented medium was greater than that of oocytes retrieved from follicles cultured in regular medium. The secretion of P4 was significantly higher on days 6, 8, and 10 in follicles cultured in BMP-15-supplemented medium. The result for E2 tended toward significance on day 12. Intracellular reactive oxygen species levels were higher and glutathione levels were lower in mature oocytes from the in vitro culture than in mature oocytes from an in vivo control. A 3D culture system using an alginate matrix and supplemented with BMP-15 effectively improves the outcomes of in vitro ovarian follicle culture.